Fostering transdisciplinary research for sustainability in the Global South: Pathways to impact for funding programmes. - Schneider, Flurina; Patel, Zarina; Paulavets, Katsia; Buser, Tobias; Kado, Jacqueline; Burkhart, Stefanie (Humanities & Social Sciences Communications, 2023)
Advancing global sustainable development hinges on strengthening the connections between science, society, and policy, as well as addressing existing science inequalities. Research funding programmes play a pivotal role in this context, but little is known about how they can actively nurture required transformations of the science systems. In this paper, we investigate how science funders can actively promote science-society-policy interactions through transdisciplinary research (TDR) as a means to advance sustainable development in the Global South. Our primary focus is on the research funding programme "LIRA 2030 Africa". Our research has revealed three closely intertwined pathways for cultivating TDR in this context: (1) Enabling African scientists to lead high-quality TDR projects, (2) empowering African scientists to pursue a career as TDR researchers, and 3) enhancing the context conditions for doing TDR in Africa. By scrutinising the advantages and challenges associated with these pathways and their associated activities, we conclude that fostering TDR in Africa necessitates a multifaceted approach. This approach entails a combination of measures, such as providing research grants, offering TDR and leadership training, fostering networks, developing institutions, and facilitating collaboration across various funders.